Вибір антенних систем у складі засобів пеленгації БЛА тактичного (окопного) рівня - Бохан, І. А.; Тухтаров, В. Б. (ХНУРЕ, 2024)
This work provides an overview of the antennas in modern radio direction finding systems from world leaders - companies Rohde & Schwarz (Germany) and TCI (USA).
Keywords: пеленгація БЛА; БЛА тактичного (окопного) рівня